Effect of dietary supplementation of different strains of Streptococcus lactis on the biological performance of broilers - BHATT, R S; KATOCH, B S; DOGRA, K K; GUPTA, R; SHARMA, K S; SHARMA, C R (The Indian Journal of Animal Sciences, 2013)
The dietary supplementations (6.9 x 108 celll/kg feed) of 4 strains (3 from HPK V. Pal am pur and 1 from CFTRI. Mysore) of Streptococcus lactis were undertaken to study the biological performance of Starbro broilers up to 6 weeks of age. SI strain procured from the CFTRI, Mysore, was the most effective because it showed significantly (P